2013
DOI: 10.1002/cncr.28081
|View full text |Cite
|
Sign up to set email alerts
|

Close margin alone does not warrant postoperative adjuvant radiotherapy in oral squamous cell carcinoma

Abstract: BACKGROUND: There are major variations between institutions regarding postoperative adjuvant therapy for adverse features in patients with oral squamous cell carcinoma (SCC). The authors' practice has been to not recommend any adjuvant therapy on the basis of close (<5 mm but uninvolved) margins unless there are additional adverse features. The primary objective of this study was to assess whether the local control achieved in this patient cohort was acceptable. METHODS: In this single-institution, retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 21 publications
2
60
0
Order By: Relevance
“…29,33 Figure 3 shows the stratification of the cumulative effect of each of the adverse features. It also identifies the better prognostic group resulting in a better estimated 5-year survival.…”
Section: Discussionmentioning
confidence: 99%
“…29,33 Figure 3 shows the stratification of the cumulative effect of each of the adverse features. It also identifies the better prognostic group resulting in a better estimated 5-year survival.…”
Section: Discussionmentioning
confidence: 99%
“…A study done by Ch'ng et al demonstrated that patients who had close surgical margins show acceptable local control without post-operative adjuvant therapy [21]. However, even the margins which are apparently histologically free of tumour, may demonstrate molecular changes at the margins which could account for recurrence.…”
Section: Rt*recur Cross Tabulationmentioning
confidence: 99%
“…Wong et al [30] suggested that surgical margins within 2 mm should be considered the cut-off for recommendation of PORT. Ch'ng et al [31] also have concluded that patients with close margins had acceptable local control without PORT in the absence of other risk factors.…”
Section: Discussionmentioning
confidence: 99%